The use of multispectral imaging to distinguish reactive urothelium from neoplastic urothelium - Christopher Michael Gilbert; Anil Parwani (Elsevier, 2010)
Context: The interpretation of urothelial atypia in a setting of chronic inflammation and reactive changes can prove difficult with small biopsies. Limited recuts lessen the efficacy of ancillary studies such as CK20, P53 and CD44 in these instances. Objective: To evaluate a triple-immunostain with the assistance of multispectral microscopy. Design: Fifty-three bladder biopsies with previous diagnosis of benign/reactive, dysplastic, carcinoma in situ or carcinoma were prepared using a triple-immunostain cocktail consisting of CK20, P53 and CD44. Three control stains were used for the purpose of creating a spectral library for the Nuance CRI Flex microscopy system. All specimens were interpreted by light microscopy, processed with the Nuance 2.71 software, and CK20 and P53 were scored blinded to the case diagnoses. CD44 was not scored as it proved difficult to interpret in many cases. Results: The results demonstrated that it was possible to separate CK20, P53 and the counterstain that were co-localized in the biopsies. Separation of the stains demonstrated a correlation of p53 and CK20 dual expression in biopsies diagnosed as carcinoma. Low or undetectable levels of expression were seen in biopsies later diagnosed as reactive or benign. Conclusion: The combination of multispectral microscopy and multiple immunostain cocktails form a powerful and useful tool for the interpretation of small biopsies with faint or difficult to interpret staining and for cases with limited material such as small-bladder biopsies.